Vitamin K in Vertebrates’ Reproduction: Further Puzzling Pieces of Evidence from Teleost Fish Species - Beato, Silvia (Biomolecules, 2020)
Vitamin K (VK) is a fat-soluble vitamin that vertebrates have to acquire from the diet, since they are not able to de novo synthesize it. VK has been historically known to be required for the control of blood coagulation, and more recently, bone development and homeostasis. Our understanding of the VK metabolism and the VK-related molecular pathways has been also increased, and the two main VK-related pathways—the pregnane X receptor (PXR) transactivation and the co-factor role on the γ-glutamyl carboxylation of the VK dependent proteins—have been thoroughly investigated during the last decades. Although several studies evidenced how VK may have a broader VK biological function than previously thought, including the reproduction, little is known about the specific molecular pathways. In vertebrates, sex differentiation and gametogenesis are tightly regulated processes through a highly complex molecular, cellular and tissue crosstalk. Here, VK metabolism and related pathways, as well as how gametogenesis might be impacted by VK nutritional status, will be reviewed. Critical knowledge gaps and future perspectives on how the different VK-related pathways come into play on vertebrate’s reproduction will be identified and proposed. The present review will pave the research progress to warrant a successful reproductive status through VK nutritional interventions as well as towards the establishment of reliable biomarkers for determining proper nutritional VK status in vertebrates.